Precise and low-complexity method for underwater Doppler estimation based on acoustic frequency comb waveforms - Li, Jie; Qian, ZhiWen; Hong, DeYue; Zhai, JingSheng (Frontiers in Marine Science, 2024)
Ocean observation has experienced rapid development in recent decades due to its pivotal role in resource exploration and scientific research. However, ocean observation is hampered by the estimation of underwater Doppler factors, which requires balancing high accuracy and low complexity. This paper proposes a novel Doppler-sensitive acoustic frequency comb (AFC) to estimate the Doppler factor. The Combined Uneven Uncertainty (CUU) method based on AFC can provide a lower uncertainty of less than 9.6×10 -6 and surpass the "picket fence effect" (PFE) ceiling of 3.2×10 -5 in the absence of noise. Compared with the traditional frequency estimation methods using single-tone signals, the use of AFC signals significantly improves the utilization of the spectrum and increases estimation accuracy without additional computational effort. The results show that the CUU method can achieve performance with a difference value of less than 3.4×10 -6 .where 𝑟𝑒𝑐𝑡 is the rectangular pulse function, t is the time, T is the pulse period, 𝑛 is an integer, 𝑚 is the number of modes, A is the power amplification factor, 𝐸 𝑛 is the amplitude of individual mode, 𝑓 𝑛 is the frequency of individual mode, 𝜃 𝑛 is the initial phase, 𝑓 𝑐𝑒𝑜 is the initial frequency, 𝑓 𝑟𝑒𝑝 is the interval frequency.